(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Chronic psychological stress is a key driver of dysregulated eating behaviors and weight gain. Central to this relationship is cortisol, a glucocorticoid hormone produced by the adrenal cortex in response to activation of the hypothalamic–pituitary–adrenal (HPA) axis. While acute stress tends to suppress appetite, chronic stress leads to sustained cortisol secretion, which alters energy balance, promotes hedonic eating, and increases visceral adiposity. This review explores the neuroendocrine and behavioral mechanisms through which cortisol influences appetite regulation, macronutrient preference, and body fat distribution, emphasizing the interplay